Case study: communication and product development driving halo effect within the CPG industry - Ramirez Pages, Alba; Polo López, Marcos; Krtolica Lukic, Aleksandra (European Public & Social Innovation Review, 2024)
Introduction: Countless innovations may not succeed, yet it is crucial for companies to innovate in order to survive. Through the years, we have seen many cases of innovation failures in the Fast-Moving Consumer Goods (FMCG) industry in Spain. This research determines the key factors driving innovation success and growth for a well-established Consumer Packaged Goods (CPC) brand. Methodology: Case study method. The research included in-depth qualitative analysis, utilizing sources such as company representatives, point-of-sale data, communication channels, and interviews with industry experts. The research is focused on explaining how the brand strategically achieved success through innovation, introducing approximately 15 products in the last 5 years. Results: Research shows that specific focus on product innovation and communication strategy are crucial, and unveils that innovation contributes to the overall success of the parent brand, that is what is called the halo effect, also the importance of a strong distribution network in the FMCG industry. Discussions: Through this study, insights on how to do successful innovation in Spain in FMCG are provided and describe the factors affecting the biggest challenge of the growth market. Conclusions: The combination of product innovation, communication strategy, and distribution has proven crucial for success in this highly competitive market.